The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1471-230x-13-137
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of epithelial integrin-linked kinase for facilitation of Citrobacter rodentium-induced colitis

Abstract: BackgroundIntegrin-linked kinase (ILK) is a serine-threonine kinase that transduces extracellular matrix-related cues into intracellular signals, with fundamental roles in cell motility, development and cancer. Recently ILK been shown to have an important role in bacterial epithelial cell attachment, through ILK-bacterial OspE binding. Here we report on the role of epithelial derived ILK in response to Citrobacter rodentium infection.MethodsC. rodentium was administered to both control and intestinal epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A correlation between invasion of C . rodentium into crypts and increased host pathology has been observed in other studies [ 43 , 44 ] and so protecting this niche against intestinal pathogens is a key function for the innate immune system.…”
Section: Discussionmentioning
confidence: 69%
“…A correlation between invasion of C . rodentium into crypts and increased host pathology has been observed in other studies [ 43 , 44 ] and so protecting this niche against intestinal pathogens is a key function for the innate immune system.…”
Section: Discussionmentioning
confidence: 69%
“…ILK, an important serine/threonine protein phosphatase, plays a key role in the regulation of signal transduction and the remodeling of the tumor ECM. 11 High expression of ILK was closely related to the occurrence and development of gastrointestinal, breast, and lung tumors. 12 15 A study by Chen et al showed that ILK could promote the process of lung cancer EMT, and silencing of ILK gene could significantly inhibit the invasion and metastasis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Systems biology approaches elucidating the ECM interactome network regulated by Trypanosoma cruzi and its gp83 ligand, which mediates trypanosome attachment and entry, have shown that activation of gp83 receptors in the cell via extracellular signal‐regulated kinase 1/2 results in up‐regulation of laminin γ 1 and thrombospondin expression to facilitate trypomastigote recruitment, enhancing cellular infection . In mice, Citrobacter rodentium infection induces osteopontin and fibronectin expression through integrin‐linked kinase activation, facilitating bacterial colonization of the intestine . High expression levels of osteopontin have also been shown to be induced in murine acute and chronic coxsackievirus B3‐myocarditis together with those of MMP‐3, TIMP1, urokinase‐type plasminogen activator and TGF‐ β 1 and, in turn, procollagen‐1 α mRNA expression and fibrosis.…”
Section: Altered Ecm Dynamics In Infection and Its Implicationsmentioning
confidence: 99%